Kind-time analysis of information for the learning and implementation of the experience in the preparation and use of sub-units of the armed forces of Ukraine - Serpukhov, Oleksandr; Makogon, Helen; Klimov, Alexej; Isakov, Oleksandr; Kovalov, Ivan; Maier, Liana; Lavrut, Tetiana (Національний технічний університет "Харківський політехнічний інститут", 2023)
The subject matter of the article is transformation of information during combat sustainment at the tactical level. The goal of the study is to develop the method of collecting primary information is at the tactical level of the system of learning and implementing the experience of training and application of units of the Armed Forces of Ukraine. The tasks to be solved are: according to the main points of information theory to analyze the information of the learning and implementing the Armed Forces of Ukraine experience system and to assess the level of its qualitative characteristics; based on the analysis of the functional information transformation during combat sustainment in the observation plan to identify flows by kind of information; to formalize the mechanism of information transformation in the learning and implementing experience system according to the “black box” principle; to develop a sample questionnaire to answer the collection of primary information located at the tactical level of the learning and implementing the Armed Forces of Ukraine experience system. General scientific and special methods of scientific knowledge are used. The following results were obtained: Estimates of qualitative characteristics were calculated to determine ways of improvement the quality indicators of information circulating information in the learning and implementing the Armed Forces of Ukraine experience system. On the analysis of the functional transformation of the combat sustainment information in theobservation plan the kinds of information were defined, namely the mechanism of transformation of information in the system was formalized according to the “black screen” principle. A toolkit in the form of detailed survey sheets wasdeveloped to collect the primary information at the tactical level of the learning and implementing the Armed Forces of Ukraine experience system and made it possible to increase estimates of qualitative characteristics about three-four times.Conclusions. Consideration of the system of learning and implementation of the experience of training and application of the Armed Forces from the point of view of the main provisions of the theory of information will allow to increase the effectiveness of the procedure, to determine the ways of improving the indicators of the quality of information. To improve the quality of incoming primary information in the learning and implementing the Armed Forces of Ukraine experience system, it is considered appropriate to develop tools for its collection in the form of detailed questionnaires. Information for the s learning and implementing experience system on the way of transformation is subjected to a procedure of certain unification, transformation and further separation according to functional characteristics for analysis. The process of preparing and conducting a battle in this case can be considered as a “black box”, which directly forms the experience.

Предметом вивчення в статті є перетворення інформації при всебічному забезпеченні бою на тактичному рівні. Метою статті є розробка методики збору первинної інформації, яка знаходиться на тактичному рівні системи вивчення і впровадження досвіду підготовки і застосування підрозділів ЗС України. Завдання дослідження: з точки зору основних положень теорії інформації провести аналіз інформації, якациркулює у системі вивчення і впровадження досвіду (ВВД) та оцінити її якість; на основі аналізу функціонального перетворення інформації при всебічному забезпеченні бою виділити у плані спостереження (зборі інформації) потоки за видами інформації; формалізувати механізм перетворення інформації у системі ВВД за принципом “чорної скрині“; розробити зразок опитувального аркуші для збору первинної інформації, яка знаходиться на тактичному рівні системи ВВД підготовки і застосування Збройних Сил України. Методологічною основою дослідження стали загальнонаукові та спеціальні методи наукового пізнання. Отримані наступні результати: Обраховані оцінки якісних характеристик для визначення шляхів удосконалення показників якості інформації, яка, циркулює в системі вивчення та впровадження досвіду Збройних Сил України. На основі аналізу функціонального перетворення інформації при всебічному забезпеченні бою у плані спостереження були виділені потоки за видами інформації, а сам механізм перетворення інформації у системі ВВД був формалізований за принципом "чорної скрині". Для збору первинної інформації на тактичному рівні системи ВВД Збройних Сил України було розроблено інструментарій її збору у вигляді детальних опитувальних аркушів, що дозволило підвищити оцінки якісних характеристик приблизно в три-чотири рази. Висновки. Розгляд системи вивчення і впровадження досвіду підготовки та застосування Збройних Сил з точки зору основних положень теорії інформації дозволить підвищити ефективність процедури ВВД, визначити шляхи вдосконалення показників якості інформації. Для підвищення якості надходження до системи ВВД первинної інформації доцільно розробити інструментарій її збору у вигляді деталізованих опитувальних аркушів.Інформація для системи ВВД на шляху перетворення піддається процедурі певного об’єднання, трансформації та подальшого розділення за функціональними ознаками для аналізу. Процес підготовки та ведення бою в цьому випадку можна розглядати як “чорню скриню”, яка безпосередньо формує досвід.
Видово-часовий аналіз інформації для вивчення та впровадження досвіду підготовки і застосування підрозділів Збройних Сил України
Keywords: Armed Forces of Ukraine; systems of experience; information theory; соmbat operations sustainment; Збройні Сили України; системи досвіду; теорія інформації; всебічне забезпечення бою